A Qualitative Study of Reading Comprehension: An Insight from Pakistani Context Bridging the Needs of Engineering Students - Mansoor, Ahmed Channa; Zaimuariffudin, Shukri Nordin; Insaf Ali, Simming; Ali Asgher, Chandio (Canadian Center of Science and Education, 2016)
This study aimed to investigate the teachers’ opinions in terms of reading comprehension instruction to the engineering students for bridging their difficulties in reading academic text in communication subject. The study was conducted in the four engineering departments of one university in Pakistan. Semi-structured interviews of 10 teachers were used as a qualitative instrument to collect data for this study to know the needs of engineering students in terms of reading comprehension. The data was analyzed through NVivo version 8 for interpretation of the results. This study provided the most promising findings to develop reading ability among engineering students. The findings revealed that teachers should use rereading text, text scanning, and text skimming strategies to develop reading comprehension ability of engineering students.